Efficacy and safety of high-viscosity cement in percutaneous vertebroplasty for treatment of Osteoporotic vertebral compression fractures: A retrospective cohort study. Issue 23 (5th June 2020) - Li, Kunpeng; Feng, Hongyong; Luo, Dawei; Zhang, Wen; Yang, Keshi; Ji, Changbin; Liu, Jinlong; Xu, Hui
Abstract : Abstract: To evaluate the efficacy and safety of high viscosity bone cement in the percutaneous vertebroplasty (PVP) for treatment of single-level osteoporotic vertebral compression fractures. Eighty patients were enrolled in this study. All patients were received PVP, and they were divided into 2 groups according to the viscosity of bone cement, either high viscosity bone cement (HV group) or low viscosity cement (LV group). Oswestry Disability Index questionnaire and visual analog scale as clinical assessments were quantified. The operative time and injected bone cement volume were recorded. The anterior vertebral height (AVH) and bone cement leakage were evaluated in the radiograph. No significant difference was observed in the operative time. Both groups showed significant improvements in pain relief and functional capacity status (visual analog scale and Oswestry disability index scores) after surgery. Less bone cement volume was injected into the the injured vertebra in the HV group and statistical significance was found between both groups. In the HV group, there was lower leakage rate and less patients of severe leakage compared with the LV group. However, the correction of AVH showed no significant differences between the 2 groups and no significant loss of AVH was observed in 2 groups. High-viscosity and low-viscosity PVP have the similar effects in improving quality of life and relieving pain. There were lower cement leakage rate and less patients of severe leakage in the PVP with high-viscosity bone cement.